KEBIJAKAN PENANGANAN PEMBIAYAAN MUḌĀRABAH BERMASALAH PADA KOPWAN BMT AN-NISA’ YOGYAKARTA - Kamal, Mustafa (Syari'ah, 2016)
This   research  analyzed  the  policy  of  KopWan  BMT  An Nisa’  Yogyakartato handle the muḍārabaḥ  problem. This research  is   including   into   descriptive   qualitative research. The data contain of the primary and secondary data   which  is  caused  the  financing  problem  and  the handling   of   muḍārabah  finance   in   KopWan  BMT  An Nisa’ and todetermineits effectiveness. The data analysis used   is  qualitative  analysis.  Based   on   the   result   of research, it was recognized that the factor which caused the problems in the costing of  muḍārabah are incorrect cost analysis, dishonesty of the costumers, uncommitted of the costumers, the bankruptcy of the costumers, and the costumers   characteristics.   The   way   to   solve   the problems   by  giving  the  suspension  firtsly  and  than Rescheduling,  Restructuring,  and  Reconditioning  and proveditworked well